Slow relaxation of the magnetization observed in an antiferromagnetically ordered phase for SCM-based two-dimensional layered compounds. Issue 10 (21st February 2017) - Kagesawa, Koichi; Nishimura, Yuki; Yoshida, Hiroki; Breedlove, Brian K.; Yamashita, Masahiro; Miyasaka, Hitoshi
Abstract : We showed 2D-layered compounds exhibiting SCM-like behavior in an AF ordered phase. By introducing counteranions with a different size, Néel temperature and spin-flip inversion field could be tuned. Abstract : Two-dimensional layered compounds with different counteranions, [{Mn(salen)}4 C6](BF4 )2 ·2(CH3 OH) (1 ) and [{Mn(salen)}4 C6](PF6 )2 ·2(CH3 OH) (2 ) (salen 2− = N, N ′-bis(salicylideneiminato), C6 2− = C6 H12 (COO)2 2− ), were synthesized by assembling [Mn(salen)(H2 O)]X (X − = BF4 − and PF6 − ) and C6 H12 (CO2 − )2 (C6 2− ) in a methanol/2-propanol medium. The compounds have similar structures, which are composed of Mn(salen) out-of-plane dimers bridged by μ 4 -type C6 2− ions, forming a brick-wall-type network of [–Mn2 –OCO–] chains alternately connected via C6 H12 linkers of C6 2− moieties. The counteranions for1 and2, i.e., BF4 − and PF6 −, respectively, are located between layers. Since the size of BF4 − is smaller than that of PF6 −, intra-layer inter-chain and inter-plane nearest-neighbor Mn⋯Mn distances are shorter in1 than in2 . The zigzag chain moiety of [–Mn2 –OCO–] leads to a canted S = 2 spin arrangement with ferromagnetic coupling in the Mn III out-of-plane dimer moiety and antiferromagnetic coupling through –OCO– bridges. Due to strong uniaxial anisotropy of the Mn III ion, the [–Mn2 –OCO–] chains could behave as a single-chain magnet (SCM), which exhibits slow relaxation of magnetization at low temperatures. Nevertheless, these compounds fall into an antiferromagnetic ground state at higher temperatures of T N = 4.6 and 3.8 K for1 and2, respectively, than active temperatures for SCM behavior. The spin flip field at 1.8 K is 2.7 and 1.8 kOe for1 and2, respectively, which is attributed to the inter-chain interactions tuned by the size of the counteranions. The relaxation times of magnetization become longer at the boundary between the antiferromagnetic phase and the paramagnetic phase.